NONALCOHOLIC FATTY LIVER DISEASE IS A CORNERSTONE OF THE CARDIOVASCULAR CONTINUUM - Yusupalieva D. B.; Nizamov U. I.; Shukurjanova S.M.; Nurillaeva N. M.; Shek A. B. (Journal of Medical Genetics and Clinical Biology, 2024)
Cardiovascular diseases (CVD) are the leading cause of mortality in most countries worldwide, including Uzbekistan. The main direction in preventing diseases and complications of the cardiovascular system (CVS) is the timely detection and correction of risk factors (RF). Non-alcoholic fatty liver disease (NAFLD) is considered one of the RFs of CVD development, including coronary artery disease (CAD). Data from numerous studies demonstrate increased cardiovascular risks and accelerated progression of liver pathology in the combination of NAFLD and CAD, however, some studies have not confirmed the worsening of outcomes. An association between NAFLD and CAD, atherosclerosis, cardiac rhythm disturbances, arterial hypertension, chronic heart failure and other CVDs has been identified. However, data from meta-analyses should be interpreted with caution due to the use of different diagnostic methods and the heterogeneity of studies included in them. Further studies are needed to clarify the relationship between CVDs and NAFLD further